PENERAPAN PENDEKATAN RME UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMP SUNAN GIRI MALANG - Arifendi, Rio Febrianto; Setiawan, Rudy; Kamhar, Muhammad Yusi; Anggarbeni, Susilo Ribut; Ote, Yohanis Ana (Universitas Tribhuwana Tunggadewi, 2023)
This study aims to determine the effect of the Realistic Mathematics Education (RME) approach to improve the learning outcomes of grade VIIa students at SMP Sunan Giri Malang. The specific purpose of the research conducted was to describe the application steps of the RME Approach to improve learning outcomes in the Material Set using two cycles of Classroom Action Research (PTK). Data collection was carried out using material validation sheets, lesson implementation plans (RPP), Student Worksheets (LKS), student activity observation sheets, teacher activity observation sheets and results from posttests at the end of the cycle. The results showed that the use of the RME approach on set material succeeded in increasing the learning outcomes of grade VIIa students at Sunan Giri Junior High School, with a completeness percentage starting from 50% and increasing in the second cycle to 91.66% with a completeness score criterion of 75, so it is known that the RME approach is able to improve student learning outcomes in class VIIa set material at Sunan Giri Junior High School and is also able to increase student learning activities during learning.